Anticancer activities of the extract from Longkong (Lansium domesticum) young fruits - Manosroi A. (2014)
Context: "Longkong"(Lansium domesticum Corr., Family: Meliaceae) is a fruit found in the south of Thailand. This plant has been used in traditional medicines. Objectives: To investigate the antiproliferative activities and the phytoconstituents of Longkong extracts. Materials and methods: Cytotoxicity and apoptotic activity of 48 extracts were tested using the SRB assay and acridine orange (AO)/ethidium bromide (EB) staining, respectively. The extracts which gave the highest anticancer activity were selected to prepare the semipurified extracts and analysis for the constituents by gas chromatographymass spectrometry (GC/MS). Results: The highest percentage yield (59.38%) was from the cold water extract of Longkong ripe fruits (RFWC). The highest total phenolic and flavonoid contents were observed in cold and hot methanol extract of Longkong stalks (STMC and STMH). The hot and cold chloroform young Longkong fruit extracts (YFCH and YFCC) exhibited a cytotoxic effect (IC50 < 1 mg/mL) against cancer cells. For apoptotic induction, YFCH demonstrated the highest activity against KB of 13.84 ± 4.21% at 0.5 mg/mL which was 0.88 and 1.35 times of cisplatin and 5-FU, respectively, while apoptotic cells in HT-29 were 8.68 ± 1.85% at 5 mg/mL, which was 0.61 and 1.43 times of cisplatin and 5-FU, respectively. YFCC showed the highest apoptotic effect against KB cells at 10.70 ± 2.15% at 0.5 mg/mL, which was 0.68 and 1.07 times of cisplatin and 5-FU, respectively. The major phytoconstituents in YFCH were hexadecanoic acid (11.53%) and ethyl oleate (10.58%). Discussion and conclusion: The crude extracts of Longkong showed anticancer activities and may provide new lead compounds for the development of anticancer products. © 2012 Informa Healthcare USA, Inc.